2020
DOI: 10.3389/fonc.2020.573502
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation and Deacetylation of DNA Repair Proteins in Cancers

Abstract: Hundreds of DNA repair proteins coordinate together to remove the diverse damages for ensuring the genomic integrity and stability. The repair system is an extensive network mainly encompassing cell cycle arrest, chromatin remodeling, various repair pathways, and new DNA fragment synthesis. Acetylation on DNA repair proteins is a dynamic epigenetic modification orchestrated by lysine acetyltransferases (HATs) and lysine deacetylases (HDACs), which dramatically affects the protein functions through multiple mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 145 publications
1
30
0
Order By: Relevance
“…Thus, chromatin organization is of paramount importance for the integrity of the genome [ 141 , 142 , 143 ]. The next level, i.e., the HDAC-dependent regulation of the expression and function of the DNA repair machinery, is a highly complex issue, since virtually all types of DNA repair mechanisms are impacted by HDACs [ 140 , 144 ]. Thus, the in-depth discussion of DNA repair proteins that have been shown to be affected by HDAC inhibitors would go far beyond the scope of this review.…”
Section: Molecular Mechanisms Of Hdaci-promoted Anticancer Effectsmentioning
confidence: 99%
“…Thus, chromatin organization is of paramount importance for the integrity of the genome [ 141 , 142 , 143 ]. The next level, i.e., the HDAC-dependent regulation of the expression and function of the DNA repair machinery, is a highly complex issue, since virtually all types of DNA repair mechanisms are impacted by HDACs [ 140 , 144 ]. Thus, the in-depth discussion of DNA repair proteins that have been shown to be affected by HDAC inhibitors would go far beyond the scope of this review.…”
Section: Molecular Mechanisms Of Hdaci-promoted Anticancer Effectsmentioning
confidence: 99%
“…However, we cannot rule out the other possibility that SIRT2 and SIRT3 might be involved in loading the RPA complex onto the ssDNA region at DSB sites. DSB end resection is catalyzed by several proteins, such as the MRE11‐NBS1‐RAD50 complex, EXO1, DNA2, BLM and CtIP (Katsuki et al., 2020), and various studies have shown that these proteins are acetylated (Balakrishnan et al., 2010; Li et al., 2020; Wang & Luo, 2017; Yuan et al., 2007). In addition, the chromatin structure is regulated by histone modifications, including acetylation, which influence the efficiency of DNA end resection reactions at DSB sites (Clouaire & Legube, 2015; Kollarovic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Human SIRT1 deacetylates the p53 transcription factor (Luo et al., 2001; Vaziri et al., 2001), the XPA nucleotide excision repair protein (Fan & Luo, 2010) and the APE1 base excision repair protein (Yamamori et al., 2010). SIRT6 and SIRT7 regulate chromatin structure by changing histone modifications and recruiting chromatin remodelers to DSB sites (Li et al., 2020; Toiber et al., 2013; Vazquez et al., 2016), and SIRT6 also functions in base excision repair (BER) (Mostoslavsky et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Nej1-3KQ acetyl-mimic mutant also shows decreased binding to the C-terminal part of Mre11 compared to wild type and the 3KR mutant, which may affect its tethering activity (S5D Fig). Importantly, Nej1 phosphorylation in response to DNA damaging agents 58 In mammals, NHEJ core factor Ku70 is known to get acetylated by CBP which inhibits DNA repair and regulates Bax-mediated cell apoptosis (61,62). We tested if yeast Ku is also acetylated in yeast cells and if it could be a non-histone target of NuA4, along with Nej1.…”
Section: Acetylation Of Nej1 By Nua4 In the Regulation Of Dsb Repair mentioning
confidence: 99%